Rancang Bangun Mesin Poles untuk Material Logam - Afriansyah, Zidan; Muliastri, Destri; Azmy, Ilham; Daniel Saragih, Albert; Eka SeptiyaniArifin, Devi (Indonesian Society of Applied Science, 2024)
The polishing machine is widely used as an instrument to shine or smooth the surface of an object, one of which is a specimen before and after the electroplating process. The objects polished with this machine become shinier and perfectly clean. This research includes several stages: (1) Design, (2) calculation and component selection, (3) fabrication and assembly of components, and (4) functional testing of each component. The results showed that the polishing machine can function well according to standards. The polishing machine that has been made works using electrical energy from a 1 HP 1 Phase motor with a power of 0.75 kW and a rotational speed of 2800 Rpm. It was concluded that this polishing machine had succeeded in restoring function and performance with several aspects of change which increased tool performance. The results on steel material show that corroded steel can turn clean and shiny after the sanding process is carried out with the polishing machine.